Incidence of rotational malalignment and its effect on functional outcome after nail osteosynthesis of unstable trochanteric fractures: a prospective cohort study. Issue 2 (26th March 2021) - Pande, Hrishikesh; Tankala, Mahendra; Basavaraj Manibanakar, Naveen; Kumar, Narinder
Abstract : Background: Trochanteric fractures are common to general, trauma, and geriatric orthopaedic practice. We undertook this study to measure the degree of malrotation after fixation of unstable trochanteric fractures and its effect on functional outcomes in an elderly patient population. Methods: With strict inclusion and exclusion criteria, a total of 58 patients were included in this analysis. Based on postoperative CT, the patients were divided into the nonmalalignment group (NMG, n=38 with rotational malalignment less than 15 degrees) and the malalignment group (MG, n=20 with rotational malalignment greater than 15 degrees). The patients returned for follow-up at 3 mo, 12 mo, and 24 mo, at which time Harris hip scores (HHS), Oxford Hip scores (OHS), Oxford knee scores (OKS) and visual analogue scores (VAS) were recorded and analyzed. Results: There were no significant differences in mean age, fracture sub types by AO Foundation/Orthopaedic Trauma Association classification (AO/OTA), number of comorbidities, time from injury to surgery, or duration of surgery in these two groups. Only the gender distribution was different, with significantly more female patients in the malalignment group. The mean malrotation in the MG and the NMG was 24.9 degrees and 7.73 degrees, respectively, which were significantly different. We found that the HHS, OHS, OKS, and VAS were significantly better in the NMG. More patients in the MG had significant gait abnormality, significant deterioration of knee function, significantly reduced ability to squat and sit cross-legged, and greater requirement of assistive devices for ambulation when compared with the NMG. Conclusions: Rotational malalignment after trochanteric fracture fixation is unavoidable despite best efforts, and these patients have a significantly poorer functional outcome when compared with patients in whom there is no malalignment. Level of Evidence: Level IV.